0720 Children with Down Syndrome and Mild OSA: Treatment with Medication versus Observation. (12th April 2019) - Yu, Wenwen; Sarber, Kathleen M; Howard, Javier J M; Huang, Guixia; Hossain, Monir; Heubi, Christine H; Simakajornboon, Narong
Abstract: Introduction: Children with Down Syndrome (DS) have a high prevalence of obstructive sleep apnea (OSA). Anti-inflammatory medications have been shown to be an effective treatment for mild OSA in otherwise healthy children. However, efficacy of medication in children with DS has not been investigated. Our aim was to examine the polysomnographic changes of children with DS and mild OSA treated with medication. Methods: A retrospective chart review was performed in children with DS (<18 years) and mild OSA (obstructive apnea-hypopnea index [oAHI] ≤5 events/hour) diagnosed by polysomnography (PSG) between 2006 and 2018. Patients were included if they had treatment with medications (nasal steroid and/or montelukast) or observation with a duration of at least 3 months and had baseline and follow-up PSGs. Demographic data, co-morbid diagnoses and PSG data were collected. Baseline and follow-up PSG parameters were analyzed. Results: Forty-five children met the criteria. In the medication group, 29 children were identified. The median age was 7.4 (IQR 4.9-9.3) years. In the observation group, 16 children were identified. The median age was 4.0(IQR 3.2-5.3) years. The median time from baseline to follow-up PSG was 14.0(IQR 10.0-22.9) months for the medication group and 10.5 (IQR 6.5-33.5) months for the observation group. There were no significant changes in the oAHI from the baseline[pre] to follow-up[post] PSG in either the medication group (2.8(IQR 2.2-3.6) [pre] vs 3.5 (IQR 1.4-4.8) [post]; p =0.25) or the observation group (2.3 (IQR 1.3-3.1) [pre] vs 2.9 (IQR 1.9-6.8) [post]; p =0.12). Similarly, there were no significant differences in AHI, oxygen nadir or ETCO2 between the groups ( p =0.07-1). Conclusion: Based on PSG parameters, our study indicates that medication therapy is not effective in children with DS and mild OSA. Several anatomical factors besides adenotonsillar hypertrophy such as hypotonia and relative macroglossia may explain the ineffectiveness of medical therapy for OSA in this population. Further prospective studies are necessary to confirm these results and to evaluate a sub-group of DS children who may benefit from medical therapy. Support (If Any): Funded by the Cincinnati Children's Research Foundation